Separation Cd2+ by Oxycelluloses and Active Pulp - Filipi, Michaela; Milichovský, Miloslav; Weidlich, Tomáš (Slovenská spoločnosť chemického inžinierstva, 2016)
Natural cellulose and carboxyl celluloses are highly hydrated substances with interesting sorption behaviour. They have the similar chemical composition, but different size of molecules and representation of COOH groups organized into a complex of supramolecular structure. Separation of Cd2+ from polluted water by use of oxycellulose hydrocolloid fibrous form was compared with dissolved carboxyl methylcellulose.
Separace iontů Cd2+ pomocí oxycelulózy a aktivované buničiny
Keywords: oxycellulose; linters; adsorption; rheosedimentation; oxycelulóza; lintry; adsorpce; rheosedimentace